-5m-3=3+5m

Simple and best practice solution for -5m-3=3+5m equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5m-3=3+5m equation:


Simplifying
-5m + -3 = 3 + 5m

Reorder the terms:
-3 + -5m = 3 + 5m

Solving
-3 + -5m = 3 + 5m

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-5m' to each side of the equation.
-3 + -5m + -5m = 3 + 5m + -5m

Combine like terms: -5m + -5m = -10m
-3 + -10m = 3 + 5m + -5m

Combine like terms: 5m + -5m = 0
-3 + -10m = 3 + 0
-3 + -10m = 3

Add '3' to each side of the equation.
-3 + 3 + -10m = 3 + 3

Combine like terms: -3 + 3 = 0
0 + -10m = 3 + 3
-10m = 3 + 3

Combine like terms: 3 + 3 = 6
-10m = 6

Divide each side by '-10'.
m = -0.6

Simplifying
m = -0.6

See similar equations:

| 2x-3.8+x=62 | | 8(4+n)=88 | | 3-bc=35 | | 5(3+n)=88 | | -2(p+1)+3=-15 | | 3x^2-6x+6x=0 | | 5(3+n)=90 | | g(0)=3(0)+2 | | (.0309+x)+27.1594637= | | 6x-3x+26=5(x+8) | | -2a+3=-2 | | 3ln(x)=15 | | 2*9-4+8*2=288 | | 5q=2p | | 10+3b-7b= | | m-2n=0 | | 3(4+n)=21 | | (4x+4)+(5x-3)+17=3x*4 | | x^2-5x+9x-12=180 | | 3(.3x+.1)+.2x= | | 3x^2+15x-108=0 | | 5p+9=2n | | -44.1+(-45.8)= | | 4t+48=t+282 | | n(7+3)=40 | | 5x-3(x-6)=6 | | -3m+6n=8 | | -3(6+9)=-6 | | 2x^2-9x-1=-8x | | (x+6)-x= | | -y=12-0 | | 4x+43=10x+55 |

Equations solver categories